Ten Years' Wanderings among the Ethiopians - Hutchinson., T.J. (Hurst and Blackett, Publishers, 1861)
Without any fear or trembling, I come before the public with my third contribution to literature on the subject of Africa. If I be accused of sketching in this volume a less favourable portraiture of the African character than I have done in either of my former works, I shall only advance the plea of never having set forth anything in my description of these people but the naked and unadorned truth as it stood before me. That I have met native Africans conscious of their own inferiority, and anxious for knowledge to develop the industrial riches of their country, I have already confessed,-that "the slave population is destined to be the future working power in drawing forth Africa resources for their own and their country's good," I still hold as an abiding faith-that I have witnessed a can• nibalistic sacrifice during the past year in one of the most import:1nt commercial ports of the Bight of Biafra, these pages will attest to the reader. More than three hundred years have passed since Shakspeare made the Prince of Morocco thus address Portia, the rich heiress in the play of the" Merchant of Venice
With sketches of the manners and customs of the civilized and uncivilized tribes, from Senegal to Gaboon
Heritage
Keywords: Ethiopians; Customs; Civilization; Senegal; Gabon